Crusted scabies due to indiscriminate use of glucocorticoid therapy in infant - Fernanda Carvalho da Rocha Lima; Ana Maria Mósca Cerqueira; Manuela Boleira Sieiro Guimarães; Carolina Barbosa de Sousa Padilha; Fernanda Helena Craide; Marina Bombardelli (Sociedade Brasileira de Dermatologia, 2017)
Abstract Crusted or Norwegian scabies is a parasitic infectious disease caused by Sarcoptes scabiei var. hominis that mainly affects immunocompromised individuals and those with neurological patients. We report a case of crusted scabies in a 4-month-old infant who had been treated erroneously for atopic dermatitis with high doses of corticosteroids. This initial misdiagnosis associated with the abusive use of corticosteroid facilitated the evolution of scabies to crusted scabies and its main complications of secondary infection and sepsis.